Business-IT Relationship Management Based on IT Services - Wieslaw BARCIKOWSKI (Communications of International Proceedings, 2021)
The operations of a company in today's market require it to adapt quickly to ongoing changes and challenges. In such circumstances, doing business without IT support is very hampered and, in an increasing number of industries, even impossible. IT systems can both facilitate core business activities and support the areas that safeguard these activities, which means that they are essential in commercial enterprises as well as public institutions. In such a situation, the quality of the relationship between the company's business departments and the IT department supporting them becomes particularly important. The paper presents the problems that occur in the cooperation of business and IT departments and their causes.  The author points out that in solving these problems, the establishment of the IT service as a fundamental element of the business-IT relationship comes to help. The paper presents the definition of an IT service and the main components of a service management system on both sides (business-IT). The author then refers to the most widely used set of Information Technology Infrastructure Library (ITIL) good practices, which indicates how to manage IT services in an enterprise. Based on the principles of the ITIL, the main components of the enterprise's organisational and information system are described, on the basis of which modern relations between the business part of the company and the IT department supporting it should be built to guarantee the quality of support offered by IT systems, which such support should be consistent with the current needs of business.
Keywords: Business-IT relations; IT service management; IT service life cycle; ITIL